(3JWHjbGJ aj EOGQI GdLhOI GdTGedI (B/s - (3GdYdj, YHO GdSJGQs ((3YeGf(B: s (3OGQ GdeSjQI(B, s, 2010)
(3eaghe h WHjYI GOGQI GdLhOI GdTGedI , cdaI GdGfJGL , GdeOGNd GdadSajI dGOGQI GdLhOI GdTGedI , GdJNWjW h GdSjWQI Ydi GdLhOI (B: (3OhQI GdLhOI , COhGJ h dhMGJ GdSjWQI Ydi GdLhOI , HQGeL bHhd GdYjfI , GdCOhGJ GdMOjKI aj JNWjW eDTQGJ GdLhOI , COhGJ GdLhOI aj efXeGJ GdNOeI , GdebGQfI GdeQLYjI h efXeI GdehGUaI GdOhdjI (B.s
(3eQGLY U(B.361 (3; edGMb U(B.365s
Keywords: (3EOGQI GdGfJGLs; (3GdEjRhs; (3VHW GdLhOIs